Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.17221/213/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage on texture and microbiological stability of o-w emulsions with inulin

Abstract: Glibowski P., Kordowska-Wiater M., Glibowska A. (2011): Effect of storage on texture and microbiological stability of o-w emulsions with inulin. Czech J. Food Sci., 29: 137-144.The aim of this study was to characterise the effect of storage at 8°C on the texture and microbiological stability of oilin-water solid emulsions containing inulin (20% w/w) and rapeseed oil (20% w/w). The samples were analysed within 24 h from the production and after 7, 14, 28, 42, and 56 days of storage. Whey protein isolate (3% w/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
(29 reference statements)
0
10
0
1
Order By: Relevance
“…However, our results have shown that the samples, which had the same SFC values, various crystal types and/or network structures that are formed upon crystallization of hard fats can result in variability in hardness and therefore the viscosity (Braipson-Danthine and Deroanne, 2004). The viscosity was highly correlated with the hardness of samples (Glibowski et al, 2008); however, there are studies that reported an increase in viscosity during storage, for instance Glibowski et al (2011). …”
Section: Effects Of Ph Values On the Viscosity Of B-lfs And C-lfsmentioning
confidence: 65%
See 2 more Smart Citations
“…However, our results have shown that the samples, which had the same SFC values, various crystal types and/or network structures that are formed upon crystallization of hard fats can result in variability in hardness and therefore the viscosity (Braipson-Danthine and Deroanne, 2004). The viscosity was highly correlated with the hardness of samples (Glibowski et al, 2008); however, there are studies that reported an increase in viscosity during storage, for instance Glibowski et al (2011). …”
Section: Effects Of Ph Values On the Viscosity Of B-lfs And C-lfsmentioning
confidence: 65%
“…Moreover, the differences in all pH treatments during the storage periods were increased significantly (P<0.05) due to the post-crystallization processes (Alexa et al, 2010), and to the changes in the β-structure of fat crystals during the storage periods (Kolanowski et al, 2004). However, Glibowski et al (2011) found that the viscosity of O/W emulsions with inulin increased during storage due to the conformational changes in the inulin chains.…”
Section: Effects Of Ph Values On the Hardness Of B-lfs And C-lfsmentioning
confidence: 91%
See 1 more Smart Citation
“…Other researchers had reported the effect of polyphenols (Yuan et al, 2012) and inulin (Bosscher, Loo, & Franck, 2006) on microbial growth inhibition. Besides, Glibowski, Kordowska-Wiater, and Glibowska (2011) reported an enhanced shelf-life of low-fat preserved products using inulin. Given that, JAP is composed of polyphenols and inulin, it can be added to food products to extend shelf-life.…”
Section: Microbiological Qualitymentioning
confidence: 99%
“…Inulin is not hydrolysed by human gastrointestinal enzymes and is delivered undigested in colon and behaves as a prebiotic (Glibowski, Kordowska-Wiater, & Glibowska, 2011;Rastall, 2010;Tuohy, 2007).…”
Section: Introductionmentioning
confidence: 99%